1975
DOI: 10.1002/bjs.1800620417
|View full text |Cite
|
Sign up to set email alerts
|

The cholecystokinin test: An assessment

Abstract: A cholecystokinin (CCK) test was performed on 13 female patients who were thought to be having attacks of gallbladder pain and in whom at least one cholecystogram had been normal. In 10 of these patients the CCK test was performed during the course of a repeat cholecystogram in order to assess the effect of CCK on gallbladder contraction. There was no constant relationship between a positive test and gallbladder contraction as measured radiographically. Cholecystectomy was undertaken in 9 patients and of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…3 Unfortunately, most studies9 11 13-18 report the results of cholecystectomy only on patients who had a positive test (pain reproduced after CCK administration) or those who had a reduced gall bladder ejection fraction, and the rate of symptom relief after surgery in these series varies from 70 to 94%. Only a few studies2 19 20 have reported the results of cholecystectomy on patients who had a negative test or those who had normal gall bladder ejection fractions, and all have failed to show a difference in the symptomatic outcome after cholecystectomy when compared with the CCKPT positive patients; our study confirms these results. An important study by Rhodes and coworkers5 has examined the value of the CCKPT and showed that symptom relief from cholecystectomy was not predicted by this test.…”
Section: Discussionsupporting
confidence: 80%
“…3 Unfortunately, most studies9 11 13-18 report the results of cholecystectomy only on patients who had a positive test (pain reproduced after CCK administration) or those who had a reduced gall bladder ejection fraction, and the rate of symptom relief after surgery in these series varies from 70 to 94%. Only a few studies2 19 20 have reported the results of cholecystectomy on patients who had a negative test or those who had normal gall bladder ejection fractions, and all have failed to show a difference in the symptomatic outcome after cholecystectomy when compared with the CCKPT positive patients; our study confirms these results. An important study by Rhodes and coworkers5 has examined the value of the CCKPT and showed that symptom relief from cholecystectomy was not predicted by this test.…”
Section: Discussionsupporting
confidence: 80%
“…Provocation of an attack of pain with cholecystokinin is said to be of help in establishing a diagnosis of pain of biliary origin (Cozzolino et al, 1963;Valberg et al, 1971). We have used this test in some of our patients and have reported upon it previously (Reid et al, 1975). However, we feel that the clinical evidence is such that the clinician should be willing to make a diagnosis of gallbladder origin for pain and to recommend cholecystectomy in spite of negative X-rays when there is typical biliary colic, when all other causes have been excluded and the symptoms are severe.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous CCK peptides – mainly as sulfated CCK‐8 and the non‐sulfated CCK‐4 – have been used for decades for examination and occasionally for therapy of dysfunctions and disease in different organs; for example, for gallbladder emptying in biliary dyskinesia 147 ; for pancreatic enzyme secretion in exocrine pancreatic disease 148,149 ; and later as panicogenic substances for pathophysiological studies of panic/anxiety attacks 150–153 …”
Section: Cholecystokinin: Extraintestinal Expression and Clinical Sig...mentioning
confidence: 99%